2005
DOI: 10.1002/bjs.4758
|View full text |Cite
|
Sign up to set email alerts
|

Effective follow-up for recurrence or a second primary cancer in patients with early gastric cancer

Abstract: Clinicopathological features of patients with early gastric cancer can be used to identify those most at risk of developing either recurrence or a second primary cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
40
3
3

Year Published

2008
2008
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(52 citation statements)
references
References 16 publications
4
40
3
3
Order By: Relevance
“…Thus, it showed older age was significantly related to the progress of GC recurrent. However, it is not in agreement with previous study which reported age at diagnosis as an independent factor for recurrence of early gastric cancer (Ikeda et al, 2005). Marrelli et al, also showed the age at diagnosis as a significant risk factor affected on the GC recurrence (Marrelli et al, 2005).…”
Section: 2639 Gastric Cancer Recurrence and Associated Factors In Irancontrasting
confidence: 61%
“…Thus, it showed older age was significantly related to the progress of GC recurrent. However, it is not in agreement with previous study which reported age at diagnosis as an independent factor for recurrence of early gastric cancer (Ikeda et al, 2005). Marrelli et al, also showed the age at diagnosis as a significant risk factor affected on the GC recurrence (Marrelli et al, 2005).…”
Section: 2639 Gastric Cancer Recurrence and Associated Factors In Irancontrasting
confidence: 61%
“…In these two patients, one patient underwent total gastrectomy after endoscopic treatment, and endoscopic treatment continues in the other patient. The frequency of multicentric gastric cancer is estimated overall as 2-19% (Arai et al 1992;Suzuki et al 1995), and rate of metachronous gastric cancer after gastrectomy for early gastric cancer is estimated to be 0.5-3% (Ikeda et al 2005;Nozaki et al 2010). Results in the present study indicate a predisposition to multicentric gastric carcinogenesis in patients with FAP.…”
Section: Discussionmentioning
confidence: 47%
“…When partial gastrectomy is performed for removal of the primary cancer, the metachronous cancer can be called remnant gastric cancer [1][2][3][4]. It has been reported that the incidence of metachronous gastric cancer after partial gastrectomy for early gastric cancer is 0.6-3.0 % [1,[4][5][6].…”
Section: Introductionmentioning
confidence: 99%